Associations of Reversal Learning Performance With Personality Disorder Profile and Drug Abuse History in a Sample of Prison Inmates. - Martín-Ríos, Raquel; Perales, José C.; López-Torrecillas, Francisca; Muñoz López, Lucas (Assessment, 2025)
Prison inmate samples present a high prevalence of impulsivity- and compulsivity-related behavioral problems. The Probabilistic Reversal Learning Task (PRLT) is a useful tool to assess decision-making, and we explore its associations with inmates' personality disorder (antisocial personality disorder, APD; obsessive-compulsive personality disorder, OCPD; or both) and history of drug abuse. Mixed-effects methods were used to model acquisition and reacquisition curves across PRLT, in a sample of 275 prison inmates diagnosed with OCPD, APD, or both. Two aspects were assessed: general discrimination learning and decision-making inflexibility. Participants with a mixed personality disorder profile showed a clear pattern of decisional inflexibility. A history of drug abuse was associated with a general poorer performance but not with decision-making inflexibility. Inability to adapt to changing contingencies, and thus to adverse consequences of previously rewarded choices, was not linked to compulsivity, as hypothesized to be present in OCPD and substance use disorders, but to the mixed APD/OCPD profile.